Microalbumin excretion and outcome in children with multicystic dysplastic kidney - ALPAY, HARİKA (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2012)
Aim: To present the long-term follow-up results of children with multicystic dysplastic kidney (MCDK) and urinary microalbumin excretion levels in order to evaluate whether there is an increased risk of renal damage or not. Materials and methods: Thirty-three children with the diagnosis of MCDK who had been followed up by the nephrology outpatient clinic between 2002 and 2009 were invited to participate in the study. Twenty-six healthy children were investigated as a control group for microalbumin/creatinine ratio (mu g/g creatinine). The mean age at diagnosis, the duration of follow-up, accompanying urinary tract abnormalities, attacks of urinary tract infection (UTI), contralateral kidney size, and urinary microalbumin levels were investigated. Results: The mean age of the patients with MCDK and the mean duration of follow-up were 6.5 +/- 3.9 years and 35 months (range 2-96) months, respectively. The most common urinary tract abnormality was vesicoureteral reflux (VUR), with a rate of 34%. Thirty-nine percent of the children experienced UTI during follow-up. The compensatory renal hypertrophy of the contralateral kidney was 24% at 6 months and 68% at 12 months. Sixteen patients (59%) had an increased microalbumin/creatinine ratio (>30 mu g/mg creatinine). Microalbumin/creatinine ratio was higher in patients with MCDK than it was in the controls (P = 0.001). Conclusion: Microalbuminuria and VUR are not rare in children with MCDK. Systematic follow-up of these patients is recommended to identify those at risk of contralateral renal damage.
Keywords: Multicystic dysplastic kidney; vesicoureteral reflux; microalbuminuria; contralateral kidney abnormality; outcome; CONTRALATERAL KIDNEY; RENAL AGENESIS; EXPERIENCE; MANAGEMENT